OGG1-initiated base excision repair exacerbates oxidative stress-induced parthanatos - Wang, Ruoxi (Cell Death Dis, 2018)
Oxidative stress-induced DNA damage has been well acknowledged as a major cause leading to cell death, which is etiologically linked to ischemic injury and degenerative alterations. The most common oxidation product of DNA is base lesion 8-oxo-7,8-dihydroguanine (8-oxoG), which is repaired by 8-oxoG glycosylase1 (OGG1)-initiated baseexcision repair (BER) pathway (OGG1-BER); however, the role of OGG1-BER in oxidative stress-induced cell death is poorly investigated. DNA strand breaks and apurinic/apyrimidinic (AP) sites are effective substrates to activate DNA damage sensor poly(ADP-ribose) polymerase 1 (PARP1). Overactivation of PARP1 is associated with apoptosis-inducing factor (AIF)-mediated and caspase-independent cell death (parthanatos). We hypothesized that after an excessive oxidative insult, OGG1-BER-generated strand breaks result in hyperactivation of PARP1 and consequently cell death. To test, wild type, knockout, siRNA-depleted MEFs and neuroblastoma cells, or those expressing repair-deficient OGG1 mutants were oxidatively stressed and the role of OGG1 was examined. Results showed that OGG1-BER further increases the levels of ROS-induced DNA damage by generating repair intermediates, leading to PARP1 overactivation and cell death. Cells lacking or expressing repair-deficient OGG1 showed lower levels of DNA strand lesions, PARP1 activation, and nuclear translocation of apoptosis-inducing factor, resulting in the increased resistance to ROS-induced parthanatos. These results suggested that OGG1 guards genome integrity through either lesion repair or elimination of cells with malignant potential, to maintain the homeostasis of the host, which might depend on the magnitude of guanine oxidation.